2009
DOI: 10.3989/scimar.2009.73s2115
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infection levels by <em>Anisakis</em> spp. larvae (Nematoda: Anisakidae) in the black scabbardfish <em>Aphanopus carbo</em> (Osteichthyes: Trichiuridae) from Portuguese waters

Abstract: CiiMar, Centro interdisciplinar de investigação Marinha e ambiental, universidade do Porto, rua dos Bragas, 289, 4050-123 Porto, Portugal.suMMarY: Aphanopus carbo, black scabbardfish, specimens from 3 Portuguese regions (the mainland, Madeira and the azores) during four (mainland and Madeira) or two (azores) seasons of the year were examined for the presence of Anisakis. all the fish examined (n=287) were infected with Anisakis l 3 larvae (prevalence = 100%). significant geographical differences in intensity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Studies on the biology of black scabbardfish, mainly from Portuguese populations, in clude parasite (Costa et al, 1996(Costa et al, , 2000(Costa et al, , 2003aPontes et al, 2005;Cruz et al, 2009), distribution (Parin, 1986, fisheries (leite, 1989;Martins and Ferreira, 1995;gordon, 2001), age and growth (Williams and Bedford, 1974;Morales-nin and Sena-Carvalho, 1996;Morales-nin et al, 2002) and reproduction (Figueiredo et al, 2003). the proposal for the existence of more than one stock among these populations of black scabbardfish in Portuguese waters has already been discussed using fish genetic analysis of mitochondrial dna variation of part of the cytochrome b gene.…”
mentioning
confidence: 99%
“…Studies on the biology of black scabbardfish, mainly from Portuguese populations, in clude parasite (Costa et al, 1996(Costa et al, , 2000(Costa et al, , 2003aPontes et al, 2005;Cruz et al, 2009), distribution (Parin, 1986, fisheries (leite, 1989;Martins and Ferreira, 1995;gordon, 2001), age and growth (Williams and Bedford, 1974;Morales-nin and Sena-Carvalho, 1996;Morales-nin et al, 2002) and reproduction (Figueiredo et al, 2003). the proposal for the existence of more than one stock among these populations of black scabbardfish in Portuguese waters has already been discussed using fish genetic analysis of mitochondrial dna variation of part of the cytochrome b gene.…”
mentioning
confidence: 99%
“…The lack of significant values for correlation between intensity of anisakids and host data was also recorded by Mladineo and Poljak (2014) for S. colias and Sardina pilchardus in the Adriatic Sea, and by Costa et al (2004) for Pagellus bogaraveo off Madeira Island. By contrast, Cruz et al (2009) recorded a significant increase in anisakid intensity according to the host length for Aphanopus carbo off Sesimbra (mainland) and Madeira Islands, Portugal. Additionally, Chou et al (2011) found significantly higher intensity of Anisakis larvae in larger and older spotted mackerel (Scomber australasicus) off the Taiwanese coast.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, in Moroccan waters, prevalence of anisakids in S. colias varied from 57% to 67.9% (Abattouy et al 2011). High prevalence values were also recorded for anisakids of other fish species from the Portuguese mainland, such as the blue whiting (Micromesistius poutassou, 77.7%), the black scabbardfish (Aphanopus carbo, 100%) (Cruz et al 2007(Cruz et al , 2009) and the blackspot seabream (Pagellus bogaraveo, 100%) (Hermida et al 2012). Moreover, Costa et al (2004) also reported a high prevalence (89.6%) for the blackspot seabream off Madeira Islands, Portugal.…”
Section: Discussionmentioning
confidence: 95%
“…ziphidarum Pagi, Nascetti, Webb, Mattiuci, Cianchi & Bullini, 1988, Pagellus bogaraveo, most larvae encapsulated in fish body cavity, mesenteries, on the ouside of the viscera, Hermida et al (2012b , Saraiva et al (2000b), Silva & Eiras (2003), MacKenzie et al (2008), Cruz et al (2005Cruz et al ( , 2007Cruz et al ( , 2009, (Freitas et al 2009), Santos et al (2009, Hermida et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Anisakis sp., Aphanopus carbo, Helicolenus dactylopterus, digestive tract, surface of viscera, Cruz et al (2009.…”
Section: Nematodamentioning
confidence: 99%